IMPLEMENTASI AJARAN KEPEMIMPINAN HINDU PADA EPOS RAMAYANA DALAM PEMBERDAYAAN PEMERINTAHA DESA BAKBAKAN, KECAMATAN GIANYAR, KABUPATEN GIANYAR - Ni Ketut Puspita Sari; I Nyoman Ariyoga (Maha Widya Duta : Jurnal Penerangan Agama, Pariwisata Budaya, dan Ilmu Komunikasi, 2022)
The professionalism of the leader is very much needed, considering that his position is very important, so that the leadership spirit should be instilled and developed in managing the organization. The village government is an official government institution whose level is in every village in Indonesia, has the function to carry out the affairs of the interests of the local community in relation to government affairs in the state of Indonesia. Bakbakan village is one of the villages in the Gianyar sub-district, Gianyar district, this village was chosen as the focus of research because one of the village heads in managing the governance of his village by prioritizing Hindu leadership. This research was conducted to make a practical contribution for village leaders who are Hindus to always carry out swadharma (obligations) departing from the teachings of Hinduism. Data collection techniques in this study consisted of observations to research locations, interviews, literature studies, namely determining the concept of Asta Bratha's teachings in the Ramayana book and related literacy. Documentation is looking back at the document notes and photos of the village head who is carrying out his duties in the office and in the midst of the community. The implementation of the asta bratha teachings applied in leadership at the Bakbakan Village Office, Gianyar District, Gianyar Regency by imitating the attributes of gods consisting of: Indra Brata, Yama, Brata, Candra Brata, Surya Brata, Bayu Brata, Kuwera Brata, Baruna Brata , Agni Brata. The eight asta brata leadership are guidelines for bakbakan village heads in carrying out their duties as village leaders who are submissive and obedient to Pancasila, the 1945 Constitution, the Unitary State of the Republic of Indonesia and Bhineka Tunggal Ika. In carrying out his leadership, the Bakbakan village head prioritizes the interests of the community, improves community welfare, minimizes unemployment, improves education, and creates peace in the Bakbakan village environment.Key Word: Implementation, Hindu Leadership, Ramayana, Bakbakan Village Government